PELATIHAN GURU PROFESIONAL”MERDEKA BELAJAR” MELALUI COLLABORATIVE LEARNING BAGI GURU SEKOLAH MENENGAH DI KOTA PAGARALAM - Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Inderawati, Rita; Kurniadi, Elika; Lisnani, Lisnani; Rawani, Dewi; Gustiningsi, Tria; Malalina, Malalina; Herlina, Rini; Rahayu, Chika; Sari, Arika; Septimiranti, Delia (UNIVERSITAS PGRI MADIUN, 2023)
Abstract.Integrated Community Service (PKM) is a form of service that accommodates a series of activities as a whole. Assistance in making RPP independent learning in a cultural context on geometry material for teachers of SMP, SMA and SMK in Pagar Alam. The purpose of this service activity is to assist teachers in designing appropriate independent learning lesson plans through the use of cultural contexts, especially on geometry material. The participants of the integrated PKM activity consisted of 49 people but at the time of mentoring it was only attended by 28 participants. The service activity was carried out for 2 days, on October 5-6, 2021. The methods used during this mentoring activity were the method of presentation, discussion, interactive question and answer, and recitation. The data collection technique used a questionnaire/questionnaire given through a google form consisting of an activity evaluation questionnaire and a participant satisfaction questionnaire for all integrated PKM activities. The results of this service activity showed that 73.48% of the participants had understood the material presented by the resource person. In addition, participants stated that this activity was useful for them, especially in making RPP independent in learning to use certain contexts. Abstrak.Guru professional ‘Merdeka Belajar’ diharapkan dapat mengembangan kemampuan professional guru yang saling membelajarkan bagi guru-guru Sekolah Menengah melalui komunitas belajar yang dilakukan secara berkolaborasi. Tujuan dari kegiatan pengabdian ini adalah mengetahui kemampuan guru Sekolah Menengah dari pelatihan program guru profesional ‘Merdeka Belajar’ melalui Collaborative Learning bagi guru Sekolah Menengah melalui MGMP Kota Pagar Alam. Peserta kegiatan PKM terintegrasi terdiri dari 66 orang guru mata pelajaran Matematika dan Bahasa Indonesia dan Bahasa Inggris. Pada Tanggal 5-6 Oktober 2021 dilakukan pelatihan dengan metode yang digunakan selama kegiatan adalah penyuluhan, tanya jawab intyeraktif, dan pembimbingan. Dengan menggunakan tes dan angket kepuasan melalui google form adalah teknik pengumpulan data yang diberikan kepada seluruh kegiatan PKM terintegrasi. Hasil dari pelatihan yang telah diberikan menunjukkan dari hasil tes 73% peserta telah dapat memahami semua materi yang telah diberikan dan dari hasil angket, menunjukkan sangat puas terhadap kegiatan pelatihan yang telah diberikan. Hal ini menunjukkanbahwa kegiatan pelatihan yang telah diberikan dapat meningkatkan kemampuan professional guru yang saling membelajarkan bagi guru-guru Sekolah Menengah. activities as a whole. Assistance in making RPP independent learning in a cultural context on geometry material for teachers of SMP, SMA and SMK in Pagar Alam. The purpose of this service activity is to assist teachers in designing appropriate independent learning lesson plans through the use of cultural contexts, especially on geometry material. The participants of the integrated PKM activity consisted of 49 people but at the time of mentoring it was only attended by 28 participants. The service activity was carried out for 2 days, on October 5-6, 2021. The methods used during this mentoring activity were the method of presentation, discussion, interactive question and answer, and recitation. The data collection technique used a questionnaire/questionnaire given through a google form consisting of an activity evaluation questionnaire and a participant satisfaction questionnaire for all integrated PKM activities. The results of this service activity showed that 73.48% of the participants had understood the material presented by the resource person. In addition, participants stated that this activity was useful for them, especially in making RPP independent in learning to use certain contexts.Keywords: Integrated Community Service, Learning Implementation Plan, Freedom of Learning, Cultural Context Abstrak.Guru professional ‘Merdeka Belajar’ diharapkan dapat mengembangan kemampuan professional guru yang saling membelajarkan bagi guru-guru Sekolah Menengah melalui komunitas belajar yang dilakukan secara berkolaborasi. Tujuan dari kegiatan pengabdian ini adalah mengetahui kemampuan guru Sekolah Menengah dari pelatihan program guru profesional ‘Merdeka Belajar’ melalui Collaborative Learning bagi guru Sekolah Menengah melalui MGMP Kota Pagar Alam. Peserta kegiatan PKM terintegrasi terdiri dari 66 orang guru mata pelajaran Matematika dan Bahasa Indonesia dan Bahasa Inggris. Pada Tanggal 5-6 Oktober 2021 dilakukan pelatihan dengan metode yang digunakan selama kegiatan adalah penyuluhan, tanya jawab intyeraktif, dan pembimbingan. Dengan menggunakan tes dan angket kepuasan melalui google form adalah teknik pengumpulan data yang diberikan kepada seluruh kegiatan PKM terintegrasi. Hasil dari pelatihan yang telah diberikan menunjukkan dari hasil tes 73% peserta telah dapat memahami semua materi yang telah diberikan dan dari hasil angket, menunjukkan sangat puas terhadap kegiatan pelatihan yang telah diberikan. Hal ini menunjukkanbahwa kegiatan pelatihan yang telah diberikan dapat meningkatkan kemampuan professional guru yang saling membelajarkan bagi guru-guru Sekolah Menengah. Kata kunci : Merdeka Belajar, Komunitas Belajar, Pengabdian Kepada Masyarakat, MGMP